A new species of the genus Amoebotricha Warren, 1901 (Lepidoptera: Geometridae: Larentiinae) from China - Kang, Jianqiu; Zhang, Ning; Teng, Junle (Zootaxa, 2026)
A new species of the genus Amoebotricha Warren, 1901 (Lepidoptera: Geometridae: Larentiinae), Amoebotricha albiapicalis sp. nov., is described from Zhejiang Prov., China. The male and female adults, genitalia, habitat, and distribution are illustrated. The new species is compared with A. hiemalis Inoue, 1989 and A. grataria (Leech, 1891).